RETRACTED : Decision support system in Predicting the Best teacher with Multi Atribute Decesion Making Weighted Product (MADMWP) Method - Solikhun, Solikhun; Windarto, Agus Perdana; Amri, Amri (Universitas Dharma Wacana, 2017)
Following a rigorous, carefully concerns and considered review of the article published in International Journal of Artificial Intelligence ResearchÂ to article entitled â€œDecision support system in Predicting the Best teacher with Multi-Attribute Decision Making Weighted Product (MADMWP) Methodâ€ Vol 1, No 1, pp. 47-53, June 2017, DOI:Â https://doi.org/10.29099/ijair.v1i1.1This paper has been found to be in violation of the International Journal of Artificial Intelligence Research Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in JURASIK(Jurnal Riset Sistem Informasi dan Teknik Informatika) Vol. 1, No. 1, pp. 56-63, 2016, Â http://ejurnal.tunasbangsa.ac.id/index.php/jurasik/article/view/9The document and its content have been removed from International Journal of Artificial Intelligence Research, and reasonable effort should be made to remove all references to this article.